2015
DOI: 10.14527/pegegog.2015.030
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Phd students' initial qualitative research experiences via their diaries

Abstract: The aim of this study is to understand initial qualitative research experience and the qualitative researcher identities they try to build via diaries they reflect. This research is a analytical research model. Research data were obtained 25 diaries which were selected by criterion sampling from 60 doctoral students' diaries that they wrote in qualitative research methods course between the years 2008 and 2014. Content analysis was applied to the data. As a result of the analysis, "becoming a qualitative resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 10 publications
0
5
0
2
Order By: Relevance
“…De Marrais et al (2018) found that in the process of learning about theory in qualitative research, students felt confusion, frustration, anger, but these were replaced with feelings of success in adopting theory. Consistently, Ersoy (2015) found that the first qualitative research experience was a unique opportunity for doctoral students to discover their personal abilities, raise awareness about personal biases, criticize themselves and think the limits of their abilities. Albeit challenging the researchers in certain terms, the research process helped them gain new insights in many aspects.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…De Marrais et al (2018) found that in the process of learning about theory in qualitative research, students felt confusion, frustration, anger, but these were replaced with feelings of success in adopting theory. Consistently, Ersoy (2015) found that the first qualitative research experience was a unique opportunity for doctoral students to discover their personal abilities, raise awareness about personal biases, criticize themselves and think the limits of their abilities. Albeit challenging the researchers in certain terms, the research process helped them gain new insights in many aspects.…”
Section: Discussionmentioning
confidence: 83%
“…According to Kalpokaite and Radivojevic (2019), qualitative research is best learned by doing, involving making decisions, mistakes, and having the patience for understanding to clarify with time and practice. Consistently, Ersoy (2015) uncovered that graduate students discovered their identities as qualitative researchers by doing and experiencing, focusing on being open-minded, striving to understand the phenomena and being patient during the research process.…”
Section: Literature Reviewmentioning
confidence: 92%
“…Doküman analizi yöntemi araştırmaya konu olan olay ve olgular hakkında bilgilerin yer aldığı yazılı ve görsel materyallerin incelenmesidir (Yıldırım ve Şimşek, 2013). McMillan (2004) göre analitik araştırmalarda araştırmanın materyali olan belgelerin, kayıtların ve dokümanların içeriği; olaylara, kavramlara, görüşlere, düşüncelere ve eserlere göre analiz edilir (akt, Ersoy, 2015). Öğretim programları eğitim bilimleri alanında yapılan araştırmalarda araştırmanın dokümanı olarak kullanılabilir (Şimşek, 2009).…”
Section: Yöntemunclassified
“…Doctoral degree programmes aim at equipping candidates with intellectual autonomy to produce new scientific knowledge. Holders of a PhD degree are supposed to conduct independent research for responding to demands regarding economic and technological growth (Anderson, Cutright, & Anderson, 2013;Ersoy, 2015;Özmen & Güç, 2013, Varış, 1972.…”
Section: Higher Educationmentioning
confidence: 99%